2018
DOI: 10.1038/s41389-018-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatostatin induces pro- and anti-apoptotic lipid accumulation in breast cancer

Abstract: Given the dependence of cancers on de novo lipogenesis, we tested the effect of fatostatin, a small molecule thought to target this pathway by blocking activation of SREBP transcription factors, in breast cancer cell lines and xenograft tumors. We found that estrogen receptor (ER) positive cells were more sensitive to fatostatin than ER negative cells and responded with cell cycle arrest and apoptosis. Surprisingly, we found that rather than inhibiting lipogenesis, fatostatin caused an accumulation of lipids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In this study, we found that fatostatin could exert a more obvious inhibitory effect on ER-positive breast cancer cells than ER-negative breast cancer cells, which was consistent with the results by Brovkovych et al 38 In addition, both Western blotting and immunohistochemistry staining demonstrated that fatostatin could significantly downregulate ER, which is worth exploring further. We wondered whether the deregulated ER resulted from the deregulation of protein synthesis or protein degradation.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that fatostatin could exert a more obvious inhibitory effect on ER-positive breast cancer cells than ER-negative breast cancer cells, which was consistent with the results by Brovkovych et al 38 In addition, both Western blotting and immunohistochemistry staining demonstrated that fatostatin could significantly downregulate ER, which is worth exploring further. We wondered whether the deregulated ER resulted from the deregulation of protein synthesis or protein degradation.…”
Section: Discussionsupporting
confidence: 92%
“…RNA was isolated and RT-QPCR performance as previously published [9] . Primer sequences are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated using Trizol according to the manufacturer's instructions (Ambion). RNA was isolated and RT‐QPCR performance as previously published . Primer sequences are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Although we cannot rule out the role of fatty acid biosynthesis, the data we present here suggest that phospholipid turnover might be involved, at least in part for the accumulation of PUFA‐TAGs. This turnover could be involved in sequestering polyunsaturated fatty acids into TAGs and lipid droplets and limit phospholipid‐induced membrane damage during apoptosis …”
Section: Resultsmentioning
confidence: 99%